Thin Films: Topotactic Metal–Insulator Transition in Epitaxial SrFeOx Thin Films (Adv. Mater. 37/2017). Issue 37 (4th October 2017) - Khare, Amit; Shin, Dongwon; Yoo, Tae Sup; Kim, Minu; Kang, Tae Dong; Lee, Jaekwang; Roh, Seulki; Jung, In‐Ho; Hwang, Jungseek; Kim, Sung Wng; Noh, Tae Won; Ohta, Hiromichi; et al.
Abstract : The real‐time evolution of the electronic phase during the topotactic phase transformation in a SrFeO x thin film is shown. In article number 1606566, Woo Seok Choi and co‐workers report the metal–insulator transition in epitaxial SrFeO x thin films. A pressure–temperature phase diagram of the topotactic transformation is constructed based on real‐time optical spectroscopy and thermodynamic calculation.